Paradoxical effects of bovine somatotropin treatment on the ovarian follicular population and in vitro embryo production of lactating buffalo donors submitted to ovum pick-up - Ferraz, Márcio Leão; Sa Filho, Manoel Francisco de; Batista, Emiliana Oliveira Santana; Watanabe, Yeda Fumie; Watanabe, Michele Rodrigues; Dayan, André; Joaquim, Daniel Carlino; Accorsi, Monica R.; Gimenes, Lindsay Unno [UNESP]; Vieira, Laís Mendes; Baruselli, Pietro Sampaio (Elsevier B.V., 2015)
The aim of the present study was to evaluate the effect of bovine somatotropin (bST; 500 mg) administration on lactating buffalo donors submitted to two different ovum pick-up (OPU) and in vitro embryo production schemes with a 7 or 14 d intersession OPU interval. A total of 16 lactating buffalo cows were randomly assigned into one of four experimental groups according to the bST treatment (bST or No-bST) and the OPU intersession interval (7 or 14 d) in a 2 x 2 factorial design (16 weeks of OPU sessions). The females submitted to OPU every 14d had a larger (P < 0.001) number of ovarian follicles suitable for puncture (15.6 +/- 0.7 vs. 12.8 +/- 0.4) and an increased (P = 0.004) number of cumulus-oocyte complexes (COCs) recovered (10.0 +/- 0.5 vs. 8.5 +/- 0.3) compared to the 7 d interval group. However, a 7 or 14 d interval between OPU sessions had no effect (P = 0.34) on the number of blastocysts produced per OPU (1.0 +/- 0.1 vs. 13 +/- 0.2, respectively). In addition, bST treatment increased (P < 0.001) the number of ovarian follicles suitable for puncture (15.3 +/- 0.5 vs. 12.1 +/- 0.4) but reduced the percentage (18.9% vs. 10.9%; P = 0.009) and the number (1.4 +/- 0.2 vs. 0.8 +/- 0.1; P = 0.003) of blastocysts produced per OPU session compared with the non-bST-treated buffaloes. In conclusion, the 14d interval between OPU sessions and bST treatment efficiently increased the number of ovarian follicles suitable for puncture. However, the OPU session interval had no effect on embryo production, and bST treatment reduced the in vitro blastocyst outcomes in lactating buffalo donors.
Keywords: OPU; bST; Embryo; IGF; Oocyte quality